2016
DOI: 10.1039/c5sc02936h
|View full text |Cite
|
Sign up to set email alerts
|

‘Traceless’ tracing of proteins – high-affinity trans-splicing directed by a minimal interaction pair

Abstract: Using a minimal lock-and-key element the affinity between the intein fragments for N-terminal protein trans-splicing was significantly increased, allowing for site-specific, ‘traceless’ covalent protein labeling in living mammalian cells at nanomolar probe concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…In fact, many groups have repeatedly observed yields of 10% or less with ncAA incorporation into transporters 36 , ion channels [37][38][39] , and G protein-coupled receptors 40,41 . Although the generally low yields observed with tPTS likely restrict the approach to applications that do not require large amounts of protein, at least some of the above limitations can be addressed by engineering more promiscuous and efficient split inteins [10][11][12]42 or by adding affinity tags to promote split intein interactions 18 . Such improvements would allow the approach to be applied to a broader complement of target proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many groups have repeatedly observed yields of 10% or less with ncAA incorporation into transporters 36 , ion channels [37][38][39] , and G protein-coupled receptors 40,41 . Although the generally low yields observed with tPTS likely restrict the approach to applications that do not require large amounts of protein, at least some of the above limitations can be addressed by engineering more promiscuous and efficient split inteins [10][11][12]42 or by adding affinity tags to promote split intein interactions 18 . Such improvements would allow the approach to be applied to a broader complement of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, tPTS has largely been conducted in vitro or restricted to bacterial expression systems, cell lysates, nuclear extracts, or selection protocols 8,[13][14][15] . Indeed, most live cell applications of PTS utilize single split inteins for the purpose of N/C-terminal tagging [16][17][18] or manipulating protein assembly/expression 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the studies presented here,t he value of the trisNTA-His-tag interaction is further revealed by its application in 1) protein tethering to membranes, [12b,64] liposomes, [6b] glass surfaces, [65] gold interfaces, [9a, 66] and nanoparticles, [67] 2) guided high-affinity protein trans-splicing and "traceless" labeling, [56] 3) stochastic sensing of single mole- Figure 5. Fori nstance,t he genetic modification of target cells,o ften the need for cell fixation before imaging,p ossible inaccessibility of the His-tag due to steric shielding or unexpected changes of protein properties (for example,d ecreased solubility,m isfolding,o rd imerization) need to be considered before implementation of this method.…”
Section: Discussionmentioning
confidence: 94%
“…The MCHs contain two to six NTA units, leading to (sub‐)nanomolar binding affinity towards a histidine tag for site‐specific labeling of targets even in a crowded cellular environment with low toxicity . The combination of high‐affinity binding properties and an ultra‐small, non‐disturbing affinity tag of smaller than 1 kDa enables 1) protein labeling with organic dyes, quantum dots, and streptavidin, 2) protein tethering to membranes, liposomes, glass surfaces, gold interfaces, and nanoparticles, 3) guided high‐affinity protein trans‐splicing and “traceless” labeling, and 4) stochastic sensing of single molecules in nanopores, single‐molecule tracking, or super‐resolution microscopy even in living cells . However, the variety of arrangements for connecting the NTA groups has led to a confusing array of MCH probes on offer, sometimes even sharing the same designation, despite a fundamentally different chemical structure.…”
Section: Figurementioning
confidence: 99%